Orchestration of Neuronal Differentiation and Progenitor Pool Expansion in the Developing Cortex by SoxC Genes - Chen, Chao; Lee, Garrett A.; Pourmorady, Ariel; Sock, Elisabeth; Donoghue, Maria J. (The Journal of Neuroscience, 2015)
As the cerebral cortex forms, specialized molecular cascades direct the expansion of progenitor pools, the differentiation of neurons, or the maturation of discrete neuronal subtypes, together ensuring that the correct amounts and classes of neurons are generated. In several neural systems, the SoxC transcriptional regulators, particularly Sox11 and Sox4, have been characterized as functioning exclusively and redundantly in promoting neuronal differentiation. Using the mouse cerebral cortex as a model, Sox11 and Sox4 were examined in the formation of the most complex part of the mammalian brain. Anticipated prodifferentiation roles were observed. Distinct expression patterns and mutant phenotypes, however, reveal that Sox11 and Sox4 are not redundant in the cortex, but rather act in overlapping and discrete populations of neurons. In particular, Sox11 acts in early-born neurons; binding to its partner protein, Neurogenin1, leads to selective targeting and transactivation of a downstream gene, NeuroD1. In addition to neuronal expression, Sox4 was unexpectedly expressed in intermediate progenitor cells, the transit amplifying cell of the cerebral cortex. Sox4 mutant analyses reveal a requirement for Sox4 in IPC specification and maintenance. In intermediate progenitors, Sox4 partners with the proneural gene Neurogenin2 to activate Tbrain2 and then with Tbrain2 to maintain this cell fate. This work reveals an intricately structured molecular architecture for SoxC molecules, with Sox11 acting in a select set of cortical neurons and Sox4 playing an unanticipated role in designating secondary progenitors.
EVALuna2:4974